Cell-surface display technology and metabolic engineering of Saccharomyces cerevisiae for enhancing xylitol production from woody biomass. Issue 7 (13th March 2019) - Guirimand, Gregory; Inokuma, Kentaro; Bamba, Takahiro; Matsuda, Mami; Morita, Kenta; Sasaki, Kengo; Ogino, Chiaki; Berrin, Jean-Guy; Hasunuma, Tomohisa; Kondo, Akihiko
Abstract : Xylitol is a major commodity chemical widely used in both the food and pharmaceutical industries. Abstract : Xylitol is a major commodity chemical widely used in both the food and pharmaceutical industries. Although the worldwide demand for xylitol is constantly growing, its industrial production from purifiedd -xylose involves a costly and polluting catalytic hydrogenation process. Biotechnological production of xylitol from biomass is a promising strategy to establish an environmentally friendly sustainable conversion process. In this study, xylitol was produced from woody Kraft pulp (KP) by using an engineered strain of Saccharomyces cerevisiae (YPH499-XR-BGL-XYL-XYN) expressing cytosolic xylose reductase (XR), along with β-d -glucosidase (BGL), xylosidase (XYL) and xylanase (XYN) enzymes co-displayed on the cell surface. All these enzymes contributed to the consolidated bioprocessing of KP to xylitol with a yield of 2.3 g L −1 (28% conversion) after 96 hours, along with a significantly reduced amount of commercial enzymes required for pre-treatment (commercial hemicellulase cocktail (CHC), [CHC] = 0.02 g-DW per g). Further improvement of the cell surface display of XYL and XYN was obtained by using a SED1 "SSS" cassette, containing the coding sequences of the SED1 promoter, the SED1 secretion signal, and the SED1 anchoring domain, to generate the improved strain YPH499-XR-BGL-XYLsss-XYNsss. This improved strain showed a significantly enhanced xylitol production capacity reaching a yield of 3.7 g L −1 (44% conversion) after 96 hours. The cellulosic content of KP residues was also significantly increased, from 78% to 87% after 96 hours of fermentation, and nanofibrillation of KP residues was observed by scanning electron microscopy. Pre-treatment and fermentation were successfully performed as a proof of concept to further scale up bio-refinery industrial production of xylitol from lignocellulose.